Predicción de diámetros superiores, sin corteza, para pináceas en la Unidad de Manejo de Olancho, Honduras [Pinus oocarpa, Pinus caribaea]. - Castañeda, F; Ramírez, M.A (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
Grosenbaugh's bark Option 2 best estimated upper stem diameter inside bark from diameter outside bark readings for two Honduran pine species. Pinus oocarpa Schiede and P. caribaea Morelet. Actual diameters inside bark were compared to diameters estimated by the three bark options using Freese’s test of accuracy.